From necessity to opportunity: Scaling bricolage across resource‐constrained environments. (28th September 2020) - Busch, Christian; Barkema, Harry
Abstract: Research summary: Enterprises in low‐resource contexts often rely on bricolage (i.e., making do by applying resources at hand to new problems). However, bricolage has traditionally been regarded as a way to temporarily get by, potentially constraining growth if continued over time. This has been explained by factors such as limited development of learning competencies. Surprisingly, we encountered a social organization appearing to use bricolage to scale extensively into a variety of locations. This puzzling observation prompted our research question: Can bricolage be scaled, and if so, how and why? We embarked on a process study of this organization, leading to a novel conceptual model of scaling bricolage: as a low‐cost replication process of heuristics, enabling fit with a diversity of local environments, as well as cross‐unit learning. Managerial summary: How do organizations emerge, survive, and scale in resource‐scarce environments? Traditional scaling models tend to rely on considerable financial resources and companies often struggle to adjust to diverse contexts. In contrast, we identified and studied an organization in Sub‐Saharan Africa that we argue used simple rules to scale bricolage—making the best out of what is at hand—successfully in diverse low‐resource contexts. Our paper provides a novel conceptual model of scaling bricolage: a low‐cost replication process of heuristics, enabling fit with a diversity of local environments, as well as cross‐unit innovation and learning.